PERBANDINGAN KEBIJAKAN PEMERINTAH INDONESIA DI ERA SUSILO BAMBANG YUDHOYONO DAN PEMERINTAH FILIPINA DI ERA BENIGNO AQUINO III DALAM PENGIRIMAN DAN PERLINDUNGAN TENAGA KERJA DI LUAR NEGERI - Sarah Nur Ramadhani (HI 16 UMY 022, 2016)
*22 This paper describes how comparative policy related to the delivery and protection of migrant workers in Indonesia and the Philippines. Both of these countries are suppliers of labor migrants in the world, but the fate suffered by each of its workforce is different. Exploitation and fraud are often trapped by Indonesian migrant workers are commonly referred to as TKI (Tenaga Kerja Indonesia). Comparison of policy between the two countries will explain how migrant workers should be well managed in order to achieve the interests of each party.